Financial Investment Decisions in India Thermal Power Sector: Lessons of Experience and Proposals for Improvement - R Jaju, Brijgopal (Digital Repository of Theses - SSBM Geneva, 2024)
Financial investment decisions in India's thermal power sector, highlighting lessons from past experiences and proposing strategies for improvement. The thermal power sector is crucial for meeting India's energy needs but faces many challenges, especially regarding financial investments. The goal of this dissertation is to analyze financial investment decisions in India's thermal power sector, learn from past experiences, and suggest ways to improve. It aims to provide actionable insights for stakeholders to enhance their investment strategies. The research uses a mixed-methods approach, combining literature review, empirical analysis, and qualitative interviews to explore factors influencing investment decisions in the thermal power sector. The study finds that regulatory frameworks, market dynamics, and sustainability considerations are crucial in shaping investment outcomes. Case studies highlight both successful strategies and common pitfalls, underscoring the need for flexible approaches. The study offers valuable insights for policymakers, investors, and other stakeholders, emphasizing the importance of informed decision-making and sustainable practices in the thermal power sector. The study concludes that continuous learning and collaboration are essential to overcoming challenges and supporting a resilient and sustainable energy future in India. The research is limited by its reliance on available data and its focus on the thermal power sector, indicating a need for ongoing research to address changing dynamics. Future research should focus on long-term studies, explore emerging technologies, and promote collaboration to support sustainable development goals in India's energy sector.